Recurrent Encephalopathy: NAGS (N-acetylglutamate synthase) Deficiency in Adults - Cartagena, A (2013)
Urea cycle disorders (UCDs) are a group of uncommon heterogeneous conditions that are often detected in childhood and only rarely in adults where the presentations are subtle or non specific with symptoms of confusion and encephalopathy. N-acetyl-glutamate synthase (NAGS) deficiency is a rare urea cycle disorder that uncommonly presents in adulthood. To date there has been no detailed neurological description of an adult onset presentation of NAGS deficiency. In this review we examine the clinical presentation and management of UCDs with an emphasis on NAGS deficiency. An illustrative case is provided. Plasma ammonia levels should be measured in all patients with unexplained encephalopathy as treatment can be life-saving. Management of this rare disorder includes protein restriction and adjunct pharmacologic treatment to reduce plasma ammonia levels. Genetic counselling remains an essential component of management of UCDs.